2012
DOI: 10.1021/jp304914e
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Evidence for Unusual Microviscosity in Imidazolium Ionic Liquid and Tetraethylene Glycol Dimethyl Ether Cosolvent Mixtures

Abstract: The rotational dynamics of coumarin 153 (C153) in imidazolium-based ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim] [PF 6 ]) and tetraethylene glycol dimethyl ether (TEGDME) mixtures across all mole fractions have been investigated to determine the local viscosity of the microenvironment surrounding the probe molecules. The excimer-to-monomer fluorescence emission intensity ratio (I E /I M ) of a well-known microviscosity probe, 1,3-bis(1-pyrenyl)propane (BPP), is also employed to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 73 publications
6
33
0
Order By: Relevance
“…12,13 Possibilities for using neat ILs to control intermolecular interactions have been suggested primarily for cyanine dye self-assemblies. 14 Studies on viscosity of ILs using fluorescent dyes has been a subject of interest, [15][16][17] and the use of fluorescent probes for understanding the structure of ILs, in general, has been recently reviewed. 18 In addition, it was shown that the viscosity of molecular organic media could control the conformation of a conjugated porphyrin dimer (PD), resulting in an array of conformations with two distinct extremes: a planar and a twisted conformation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Possibilities for using neat ILs to control intermolecular interactions have been suggested primarily for cyanine dye self-assemblies. 14 Studies on viscosity of ILs using fluorescent dyes has been a subject of interest, [15][16][17] and the use of fluorescent probes for understanding the structure of ILs, in general, has been recently reviewed. 18 In addition, it was shown that the viscosity of molecular organic media could control the conformation of a conjugated porphyrin dimer (PD), resulting in an array of conformations with two distinct extremes: a planar and a twisted conformation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1‐Alkyl‐3‐methylimidazolium hexafluorophosphate ([C n mim][PF 6 ]) is one of the most commonly used ionic liquids; the material has a structural heterogeneity from the interconnected and permeated polar and nonpolar domains when the alkyl chain is butyl or longer ( n ≥4). Polar domains are formed by charge ordering of the imidazolium rings of the cations and anions through Coulomb electrostatic interactions, and nonpolar domains arise from aggregation of alkyl chains through van der Waals interactions . For ionic liquid [C 8 mim][PF 6 ], as shown in Scheme , the long octyl chains can either come close to each other in an ordered interdigitated way or individually coil themselves retaining a relatively large free volume, as reported in our previous study .…”
Section: Resultsmentioning
confidence: 81%
“…Modulation of the physical chemistry processes in various heterogeneous systems triggered by external optical or electrical control methods is currently a subject of intense research . Many probe molecules have been optimized to improve their responsive properties towards changes in their surrounding microenvironment . A heterogeneous solvent could provide a more versatile media in which simultaneous modulation of the microenvironment of solvent and the associated physical chemistry properties (such as spectral behavior) of the solute may enable many promising applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations